The vision and the path (Volume 11) - Cercas, Javier (European Investment Bank, 2019)
What is Europe? A continent fragmented through the centuries by wars, border conflicts and cultural diversity. As Europeans, we do not have a common language or a common history, but we do have common roots, needs and ambitions. These similarities led us to fulfil what at the end of the Second World War could have been called a "reasonable utopia" - the European Union. The Spanish writer Javier Cercas investigates Europe and Europeans, our past, the conflicts, the ideologies and the people who forged Europe as we know it today. Though no final answer to all the questions can be found, the conclusion seems inevitable: Europe will be unified, naturally, sooner or later, despite all the hostility. This is the eleventh essay in the Big Ideas series created by the European Investment Bank. The EIB has invited international thought leaders to write about the most important issues of the day. These essays are a reminder that we need new thinking to protect the environment, promote equality and improve people's lives around the globe.